Spread of Aspergillus flavus and aflatoxin accumulation in postharvested maize treated with biocontrol products. (December 2019) - Kinyungu, Sharon; Isakeit, Tom; Ojiambo, Peter S.; Woloshuk, Charles P.
Abstract: Maize is a major staple crop and calorie source for many people living in Sub-Saharan Africa. In this region, Aspergillus flavus causes ear rot in maize, contributing to food insecurity due to aflatoxin contamination. The biological control principle of competitive exclusion has been applied in both the United States and Africa to reduce aflatoxin levels in maize grain at harvest by introducing atoxigenic strains that out-compete toxigenic strains. The goal of this study was to determine if the efficacy of preharvest biocontrol treatments carry over into the postharvest drying period, the time between harvest and the point when grain moisture is safe for storage. In Sub-Sahara Africa, this period often is extended by weather and the complexities of postharvest drying practices. Maize grain was collected from fields in Texas and North Carolina that were treated with commercial biocontrol products and untreated control fields. To simulate moisture conditions similar to those experienced by farmers during drying in Sub-Sahara Africa, we adjusted the grain to 20% moisture content and incubated it at 28 °C for 6 days. Although the initial number of kernels infected by fungal species was high in most samples, less than 24% of kernels were infected with Aspergillus flavus and aflatoxin levels were low (<4 ppb). Both toxigenic and atoxigenic strains grew and spread through the grain over the incubation period, and aflatoxin levels increased, even in samples from biocontrol-treated fields. Our molecular analysis suggests that applied biocontrol strains from treated fields may have migrated to untreated fields. These results also indicate that the population of toxigenic A. flavus in the harvested grain will increase and produce aflatoxin during the drying period when moisture is high. Therefore, we conclude that preharvest biocontrol applications will not replace the need for better postharvest practices that reduce the drying time between harvest and storage. Highlights: Highly infected maize at harvest is most vulnerable to spoilage during post-harvest drying period. No evidence that benefits of pre-harvest biocontrol treatments extends through a prolonged post-harvest drying period. Growth of toxigenic A. flavus strains is not inhibited in biocontrol-treated grain during postharvested incubation period. Biocontrol strains can spread from treated field to untreated fields at the same site.